Judge's Consideration In Deciding The Amount Of Child -Deported Child Caring Costs In Decision Number 266/PDT.G/2023/MS.BNA AND 267/PDT.G/2023/MS.BNA - Fatahillah, Zahrul (Universitas Islam Negeri Ar-Raniry, 2025)
Children have the right to get a living after the divorce from their parents, but the Marriage Law does not determine the amount. As a result, the panel of judges in decision Number 266/Pdt.G/2023/MS.Bna determined Rp. 1,000,000 and in decision Number 267/Pdt.G/2023/MS.Bna the amount was Rp. 1,500,000. This study aims to analyze the basis for the judge's considerations in determining the amount of post-divorce child support and a juridical review of the two decisions. This research includes juridical research. The primary legal material is the Marriage Law, decision Number 266/Pdt.G/2023/MS.Bna and decision Number 267/Pdt.G/2023/MS.Bna. data analysis was carried out qualitatively based on primary legal materials and secondary legal materials. The results of the study show that the judge's consideration in determining the amount of post-divorce child rearing costs is based on the father's ability. Father's ability is obtained based on the witnesses presented to the trial. In addition, the basis for the judge's consideration was based on the petitum of the plaintiff's lawsuit which asked the panel of judges to order the defendant to pay post-divorce childcare costs. Legally, it is justifiable to provide post-divorce childcare costs that vary from one decision to another. Article 41 of the Marriage Law, Article 105 letter b and Article 156 KHI do not limit the amount of fees that must be given, so that the decision of the panel of judges giving the total cost of raising children post-divorce amounted to IDR 1,000,000 in decision Number 266/Pdt.G/2023/MS .Bna and decision Number 267/Pdt.G/2023/MS.Bna amounting to Rp. 1,500,000 is something that is justified according to law.